Formação e atitudes sociais sobre inclusão escolar em Licenciandos de Ciências Exatas - Torres, Josiane Pereira (Universidade Federal de São Carlos, 2018)
The number of enrollments of students with disabilities has increased over the years as a result of struggles and enforcement, which has ensured that these students have access to schooling in regular education. However, national legislation may provide for such access, but it can not guarantee that teachers who will receive such students will manifest attitudes favorable to the permanence of that student in their classroom. Studies have pointed out that teachers' attitudes can be a determining factor for the success of school inclusion, and part of the construction of favorable attitudes occurs through an adequate teacher training. However, the teachers' complaint highlighting the lack of preparation to meet this student audience has been recurrent, largely because adequate training is not provided during initial training. The curricular degrees of undergraduate courses, for the most part, have not included disciplines related to inclusive education. The present study aimed to develop and implement a teacher training program to test the effect of special education thematic on the social attitudes of exact science graduates. The training program was elaborated in three units addressing the contents of Pedagogical History, Policies and Practices. A total of 88 trainees composed the sample, and were distributed in three rooms of the moodle in which the course was developed. The course environment was composed of three main tabs concentrating the three themes to be tested, and three separate virtual rooms were created. Each room began the course by a thematic, the three were approached simultaneously and interspersed. Before and after the participation of the trainees in the first unit of the course, their social attitudes were measured through the Likert Scale of Social Attitudes in relation to inclusion (ELASI). By means of statistical tests we verified that there was no statistically significant difference in the attitudes of the students for each one of the subjects tested between the rooms, as well as intra-rooms. However, it is to be considered that most of the students have already started the course with attitudes close to the extreme maximum of ELASI. During the analyzes, there were cases of decrease of scores in the post-test when compared to the pre-test, cases of the same measure of attitudes in both tests. Although the quantitative results show that the change in attitudes was not significant, there were some positive fluctuations of attitudes leading to the hypothesis that in some way the course contributed positively to the attitudes of the trainees. Outstanding cases were also analyzed qualitatively according to the respective productions during the activities. The results put us to reflect that the topics addressed in undergraduate courses present some potential to promote changes of attitudes in the graduates, but perhaps it is the moment to rethink the approach and significance given to these disciplines.
Keywords: Educação Especial; Formação de professores; Formação inicial; Atitudes sociais; Inclusão; Ciências Exatas; Special education; Teacher training; Initial formation; Social attitudes; Inclusion; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO